The Influence of Compensation and Work Quality on Employee Performance with Organizational Commitment as A Variable Intervening in BPJS Employment Karo Kabanjahe - Riwike Sinaga; Mesra B (Lafadz Jaya Publisher, 2023)
This research aims to see the effect of compensation and work quality on employee performance both directly and through organizational commitment at the BPJS Employment Karo Kabanjahe office. This type of research is associative quantitative. The number in this study was 130 employees and the sample taken was 98 employees. Data collection was carried out by distributing questionnaires and the research source was primary data. This research model uses path analysis and the measuring tool for this research uses SEM PLS version 3. The results of this research are that compensation has a positive but not significant effect on employee performance, compensation has a positive and significant effect on organizational commitment, work quality has a positive and significant effect on employee performance.